Przedsiębiorstwo w polskim systemie prawnym - Firlit, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The presented study is a presentation of the problem of the concept of enterprise in the Polish legal system. The purpose of this paper is to present the complexity of the definition of an enterprise in the light of applicable legal provisions, judicial decisions and legal dogmatics. Due to the nature of the article, the main research method will be an objective analysis of the legal order regulating the enterprise’s issues aimed at systematizing the most important issues in the presented topic
Keywords: enterprise; legal system; economic activity; enterprise components